Human resource development in Asia: capitalizing on human expertise for greater innovation and creativity Proceedings of the 10th International Conference of the Academy of HRD (Asia Chapter) - Ismail , Maimunah (Department of Professional Development & Continuing Education, Faculty of Educational Studies. Universiti Putra Malaysia, and Academy of Human Resource Development, 2011)
This study measures the internal customer satisfaction towards HRM practices and its relationship with external customer satisfaction and with other organisational outcomes such as job satisfaction, employee commitment, and turnover intention. Data was collected from five universities in the Klang Valley. There were 575 internal customers and 600 external customers participated in this study. The findings revealed that employees are satisfied with the HRM practices of their organisation. This study partially supports the hypothesis that internal customers’ satisfaction is positively related to external customers’ satisfaction.